Exploring the Pleiotropy of PCSK9: A Wide Range of Influences from Lipid Regulation to Extrahepatic Function - Wang H; Tang G; Wu J; Qin X (Journal of Inflammation Research)
Huaru Wang,1 Guodong Tang,2,3 Jianqiang Wu,4 Xuzhen Qin1 1Department of Laboratory Medicine, Peking Union Medical College Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing, 100730, People’s Republic of China; 2Department of Cardiology, Beijing Hospital, National Center of Gerontology, Institute of Geriatric Medicine, Chinese Academy of Medical Sciences, Beijing, 100730, People’s Republic of China; 3Department of Cardiology, Beijing United Family Hospital, Beijing, 100015, People’s Republic of China; 4Institute of Clinical Medicine, National Infrastructure for Translational Medicine, State Key Laboratory of Complex Severe and Rare Diseases, Chinese Academy of Medical Sciences and Peking Union Medical College Hospital, Beijing, 100730, People’s Republic of ChinaCorrespondence: Xuzhen Qin, Email qxz_01@163.comAbstract: In cardiovascular disease, the discovery of the proprotein convertase subtilisin/kexin type 9 (PCSK9) has undoubtedly opened a new chapter in regulating blood lipids. Since its first identification as a key regulator of low-density lipoprotein receptor (LDLR) degradation in 2003, the role of PCSK9 in cholesterol metabolism has been extensively studied. However, with further research, the pleiotropy of PCSK9 has gradually emerged, and its impact extends far beyond cholesterol metabolism in the liver. The purpose of this review is to systematically explore the pleiotropy of PCSK9, extending from its important role in lipid regulation to its extensive effects in extrahepatic tissues, and to reveal its potential role in cardiovascular health, nervous system function, and tumor biology. By integrating the latest research findings, this paper summarizes the complex mechanisms of action of PCSK9 in different biological processes and explores its potential and challenges as a therapeutic target.Keywords: PCSK9, pleiotropy, blood lipid regulation, extrahepatic function